培美曲塞单药或联合铂类三线及以上治疗晚期非鳞型非小细胞肺癌的临床观察 (Zhongguo Fei Ai Za Zhi, 2012)
BACKGROUND AND OBJECTIVE: Pemetrexed in combination with platinum or a single-agent has been approved for the first- and second-line treatment of non-small cell lung cancer (NSCLC). However, the role of pemetrexed therapy in the third-line and beyond treatment of NSCLC has yet to be generally accepted. The present retrospective study reports the efficacy and safety of pemetrexed in the third-line and beyond treatment of advanced non-squamous NSCLC. METHODS: A total of 46 patients with advanced non-squamous NSCLC received a combination of pemetrexed plus platinum or a single-agent after multi-line treatment failed to yield positive results. RESULTS: Of the 46 patients who participated in the study, 7 achieved partial responses, 20 reached a stage of stable disease, and 19 reached a stage of progressive disease. The over-all object response rate was 15.2% and the disease control rate (DCR) was 58.7%. The median progression-free survival time was 3.0 months. Pemetrexed in combination with platinum yielded a higher DCR than the pemetrexed plus single-agent treatment (P=0.043). Common adverse events included nausea, vomiting and myelosuppression. CONCLUSION: Administration of pemetrexed after failure of multi-line treatment is clinically beneficial to patients with advanced non-squamous NSCLC. The toxic effects of the treatment appear to be tolerable.